THE EFFECTIVENESS OF GRAMMAR TUTORING PROGRAM BASED ON STUDENTS FEEDBACK BATCH 2016 ELESP - Mulatsih, Maria Vincentia Eka (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
There were two major aspects of English Language Education Study Program students of Sanata Dharma University that needed to be improved when they spoke and wrote in English. First was their grammar and the second was their pronunciation. For solving these problems, there were two tutoring programs. As one of those two programs, grammar tutoring program needs to be evaluated. Knowing its effectiveness in helping students improvement is crucial. Based on that reason, the analysis of the result of observation and questionnaire including students feedback is one of the media to measure the effectiveness of this tutoring program. Not only does this paper deal with the qualitative result of observation, questionnaire and students feedback, it also contributes the good practices that can be applied and some aspects that are needed to improve for future tutoring programs. The result shows that 84% of the students agreed that this program helped them to improve their skill and to understand more about the grammar materials.